SPECIES COMPOSITION AND RELATIVE ABUNDANCE OF EXOPHILIC MOSQUITOES FROM KANO STATE NORTHWEST-NIGERIA - Abdullahi, Jibril Muhammad; Musa, Mustapha Dogara; Kamoru, Abdulazeez Adeniyi; Joshua, Babalola Balogun (FUDMA Journal of Sciences, 2026)
Exophilic mosquito populations play a key role in mosquito borne diseases transmission dynamics. Factors like  climate change, urbanization and deforestation are increasing abundance while interventions  target endophilic mosquitoes, potentially shifting more transmission to exophilic species.  Study on exophilic mosquito species composition and relative abundance was carried out in some parts of Kano State. The exophilic mosquitoes were collected once monthly for the period of twelve months from different  sites including  Darmanawa in Tarauni LGA, Babban Gura in Makoda LGA and Unguwar Fulani in Wudil LGA using cardboard boxes placed in an undisturbed  area of two randomly selected households  from 6 pm to 8 am. The mosquitoes  species  collected  were identified morphologically to species level with the aid of reported taxonomic guides. A total of 520 mosquitoes were collected which wer identified into 17 species across 5 genera. Higher significant (p 0.05), species (F = 1.35, p > 0.05), site (F =1.715, p > 0.05) and season (F =1.181, p > 0.05). Exophilic mosquito  populations is diverse with peak of the collection in October  and Darmanawa site had the highest number of mosquitoes.
Keywords: Exophilic,- Kano, Mosquitoes, Species composition, Relative abundance